Direct input from cochlear root neurons to pontine reticulospinal neurons in albino rat. - Nodal, F; López, D (2003)
The cochlear root neurons (CRNs) are thought to mediate the auditory startle reflex (ASR) in the rat, which is widely used as a behavioral model for the investigation of the sensorimotor integration. CRNs project, among other targets, to the nucleus reticularis pontis caudalis (PnC), a major component of the ASR circuit, but little is known about the organization of this projection. Thus, we injected biotinylated dextran amine (BDA) in CRNs to study their projections with light and electron microscopy. Also, we performed double-labeling experiments, injecting BDA in the CRNs and subunit B of the cholera toxin or Fluorogold in the spinal cord to verify that CRNs project onto reticulospinal neurons. Electron microscopy of the labeled CRNs axons and terminals showed that even their most central and thinnest processes are myelinated. Most of the terminals are axodendritic, with multiple asymmetric synapses, and contain round vesicles (50 nm diameter). Double-labeling experiments demonstrated that CRN terminals are apposed to retrogradely labeled reticulospinal neurons in the contralateral nucleus reticularis PnC and bilaterally in the lateral paragigantocellular nucleus. Analyses of serial sections revealed that multiple CRNs synapse on single reticulospinal neurons in PnC, suggesting a convergence of auditory information. The morphometric features of these neurons classify them as giant neurons. This study confirms that CRNs project directly onto reticulospinal neurons and presents other anatomical features of the CRNs that contribute to a better understanding of the circuitry of the ASR in the rat.